Why do training regimes for early childhood professionals differ? Sweden and Switzerland compared. (November 2020) - Geiss, Michael; Westberg, Johannes
In Europe, there are many different ways in which early childhood education and care professionals are trained. This article investigates how these different forms came into being. Comparing two small, prosperous European countries, Sweden and Switzerland, we analyse the developments in training regimes for early childhood professionals since the 19th century using a historical institutionalism approach. We focus on corporate actors and the institutionalization of educational structures and identify critical junctures and path dependencies. Although both countries developed a comparable diversity of training opportunities in the 19th century and early 20th century, developments since the 1950s have diverged widely. While Sweden is developing a uniform, fully academicized training structure, the Swiss case exhibits no such uniformity but is characterized by continuity and incremental change. The article traces the role played by central governments, private associations and educational reform in the development of the training of preschool personnel.